ANALISIS KELAYAKAN USAHA INDUSTRI MAKANAN KERIPIK NANGKA DI KECAMATAN TAMBANG KABUPATEN KAMPAR - Wahyu Kresnadi Putra; Rahmita Budiarti Ningsih; Deny Setiawan (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2018)
The research aims to know the feasibility of food industry jackfruit chips in Tambang District Kampar Regency and to know the problem or constraints faced in running the industry of jackfruit chips in Tambang District Kampar regency. The population and sample in this research is all industry of jackfruit chips that still active and selling in Tambang District Kampar Regency, which amounted to 13 industries. The research method used in this study is the feasibility study method, by reviewing the aspects of feasibility study that is a review on financial aspect and non financial aspect. In the non-financial aspect through a review on socio-economic aspects, as well as financial aspects through financial feasibility reviews by calculating the Net Present Value (NPV), B / C Ratio, Internal Rate of Return (IRR) and Payback Period (PP). The results of this study indicate that the review of socio-economic aspects of food industry jackfruit chips in Tambang District Kampar Regency is feasible to be run and developed, and the financial aspect analysis through business feasibility calculation shows the value of NPV 119.178.745,61 > 0, B / C Ratio 1,197 > 1, IRR value 20,84% > 12% and PP value for 3 years 1 month 24 days. From the calculation shows that the food industry jackfruit chips in Tambang Dustrict Kampar Regency feasible to run and developed.Keywords: Feasibility Study, Jackfruit Chips, NPV, IRR, B/C RATIO, PP